Pendidikan Multikultural dalam Perspektif Islamic Worldview - Muzaki, Iqbal Amar; Tafsir, Ahmad (Jurnal Penelitian Pendidikan Islam, 2018)
Educational experts have always held that multicultural education is able to address social, political, and cultural problems. Their views are based on the belief that multicultural education essentially carries themes of respect and respect for other people's cultures, respect and empathy for diversity, tolerance, willingness to live together peacefully, willingness to share. This article attempts to highlight the concept of multicultural education in the perspective of an Islamic worldview